PENINGKATAN KEMAMPUAN MENGENAL KATA MELALUI METODE BERMAIN KARTU HURUFPADA KELOMPOK B TK PERSADA TENGGARONG SEBERANGTAHUN PELAJARAN 2017/2018 - Sulaimah - Sulaimah; Hanita - Hanita (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2019)
Students in group A at Tunas harapan Tenggarong Seberang encountered difficulties in remembering number symbols. Monotone learning activity, such as writing, coloring, and drawing, without involving singing activity and playing, is considered as the cause of the issue. Therefore, a classroom action research was conducted to researcher involved twenty-one young learners, consisting oftwelve males and nine females. In this study, the researcher applied two cycles, wherein each cycle, wherein each cycle, three times treatment werw conducted. Each cycle consists of four stages; planning, implementation, observation and reflection. Having analyzed the data, it is found that students experienced progress in each cycle. At cyle 1, from first meeting to third meeting, the students’ ability in recognizing number symbols reached 53% and inclined into 81 % at the second cycle, which met the target of success indicator. To sum up, the use of wayang number is able to promote students’ ability of number symbol recognition. Therefore, it is suggested for teachers to create more creative media of teaching, to self – motivate and widen more teachers’ insight.